2018
DOI: 10.1093/jee/toy234
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Temperature for Rearing the Edible Ruspolia differens (Orthoptera: Tettigoniidae)

Abstract: Ruspolia differens Serville (Orthoptera: Tettigoniidae) is an insect with significant economic potential in Africa. However, to mass-rear this species on a large scale, the optimal rearing temperature needs to be determined. We assessed multiple performance traits for R. differens reared at seven constant temperatures, ranging from 18 to 32°C, from newly hatched nymphs to 3 wk after adult molting. The highest observed survival was at 30°C (mean survival of 86.7%), where also the development rate reached its ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 47 publications
1
12
1
Order By: Relevance
“…Therefore, it is likely that the fatty acids (or their precursors) were insufficient to build a heavy fat body with the grass inflorescence diets studied. Compared to our previous studies [ 19 , 20 ], feeding on artificial diets generally produced R. differens with relatively higher weight (0.4–0.65 g) than with natural plant diets studied here (0.41–0.45 g), which could be related to a higher fat content of artificial diets than in grass inflorescences.…”
Section: Main Textcontrasting
confidence: 86%
“…Therefore, it is likely that the fatty acids (or their precursors) were insufficient to build a heavy fat body with the grass inflorescence diets studied. Compared to our previous studies [ 19 , 20 ], feeding on artificial diets generally produced R. differens with relatively higher weight (0.4–0.65 g) than with natural plant diets studied here (0.41–0.45 g), which could be related to a higher fat content of artificial diets than in grass inflorescences.…”
Section: Main Textcontrasting
confidence: 86%
“…In addition, the fatty acid composition of R. differens can be manipulated with its diet (Lehtovaara et al, 2017; Rutaro et al, 2018a,b), i.e., with specific feeds, it can become even more suitable for human consumption. Recently, there have been attempts to develop mass‐rearing methods for this species (Lehtovaara et al, 2017, 2018; Malinga et al, 2018a,b; Rutaro et al, 2018a,b), which could prevent overharvesting of the wild populations in the long‐term. Ruspolia differens has potential for mass‐rearing in the Lake‐Victoria basin, where there are long traditions for consuming this species, but also elsewhere, as the species is nutritionally valuable due to its healthy fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…The overall acceptance scores of both leaves and inflorescence were lower for females compared to males in no‐choice experiments. Both sexes of R. differens accumulate weight as adults, but females generally gain more weight than males (Lehtovaara et al, in press) and thus should have an overall higher demand for food. Previous studies have found sex‐specific host preference or selection (Boys, ; Behmer & Joern, ; Franzke et al., ) and higher food consumption levels by females compared to male orthopterans (Delvi & Pandian, ; Unsicker et al., ).…”
Section: Discussionmentioning
confidence: 99%